2017
DOI: 10.15441/ceem.16.166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Middle East respiratory syndrome outbreak on the use of emergency medical resources in febrile patients

Abstract: ObjectiveOutbreaks of transmissible respiratory infection are suspected to have significant effects on the health of pediatric and geriatric patients. The objective was to assess the impact of the Middle East respiratory syndrome (MERS) outbreak on the use of emergency resources.MethodsAn ecologic analysis of emergency department (ED) records between September and December 2015, was performed. Data was obtained from the National Emergency Department Information System database for Korea. All demographic and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Healthcare utilization decreased in the 2003 SARS epidemic due to fear of nosocomial infection, whereas it explosively increased in the 2009 H1N1 influenza pandemic due to fear of influenza itself 23410. In the case of MERS, since the main transmission route was nosocomial transmission and the mortality rate was high, healthcare utilization decreased during the epidemic 1213. This effect was dramatic in the ER rather than other departments in hospitals, as most of the nosocomial infections occurred in a crowded ER 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare utilization decreased in the 2003 SARS epidemic due to fear of nosocomial infection, whereas it explosively increased in the 2009 H1N1 influenza pandemic due to fear of influenza itself 23410. In the case of MERS, since the main transmission route was nosocomial transmission and the mortality rate was high, healthcare utilization decreased during the epidemic 1213. This effect was dramatic in the ER rather than other departments in hospitals, as most of the nosocomial infections occurred in a crowded ER 6.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the impacts of SARS and influenza epidemics 2341011. However, although few small studies have investigated changes in healthcare utilization during the MERS epidemic in Korea,1213 no study has systematically evaluated the impact of the MERS epidemic on nationwide healthcare utilization. Furthermore, the impact of the reduction in emergency care utilization on health outcomes has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Pathway and protocols need to be in place to ensure that rapid appropriate care is provided to suspected COVID-19 children, while avoiding delay in care of non-COVID-19 patients. 9 In addition, it will be paramount to ensure patients and staff are protected from the infection and with as little exposure as possible.10 It has also become recognised that children may present with conditions not linked to COVID-19 but some, when admitted for that condition, are found to have COVID-19 positive swabs as an incidental finding. This may be a feature with the more widespread dissemination of COVID-19 throughout the population.…”
Section: Importancementioning
confidence: 99%
“…Shifts in health-seeking behaviours also contribute, with an unwillingness to access healthcare driven by concerns about contagion in hospital settings [ 8 , 9 ]. Evidence from SARS and MERS epidemics have shown that risk preventative behaviours, such as hospital avoidance, were widely practised, with fear of infection associated with avoidance of healthcare facilities [ 10 , 11 , 12 , 13 , 14 ]. Of concern was an increase in cases triaged ‘very urgent/immediate’ among those admitted; however, without presenting complaint or diagnosis, this finding is difficult to interpret [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%